Texture and microstructure characterizations of Fe-3.5wt%Si soft magnetic alloy fabricated via laser powder bed fusion - Shen, Xiaojun (2022)
Manufacturing stable grain-oriented electric steel with fewer procedures remains a challenge due to the formation of detrimental γ-fiber (〈111〉//ND) texture. In this work, Laser Powder Bed Fusion (LPBF) process was employed to obtain a strong λ-fiber (〈100〉//ND) texture in a Fe-3.5wt%Si electrical steel. The texture and microstructure were characterized by Electron Backscatter Diffraction (EBSD), Scanning Electron Microscopy/Energy Dispersive X-ray Spectroscopy (SEM/EDS) and High-Resolution Transmission Electron Microscopy (HRTEM). The EBSD results showed a strong λ-fiber texture on the top plane of Fe-Si alloy. It included {001}〈001〉 Cube texture, {001}〈110〉 rotated cube texture and {100}〈105〉 texture. With the lowest energy density, an area fraction of 16.6% γ-fiber texture was formed on the top plane. Additionally, the formation of amorphous precipitates in additively manufactured Fe-Si alloy was firstly reported. The lattice constant of 2.7975 Å was calculated in the matrix area. The work has shown LPBF can open a new door to manufacture grain-oriented electrical steel for industrial applications.